2004
DOI: 10.1029/2003gl018386
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of water cloud reflectance: A comparison of measurements and 1D theory

Abstract: [1] Bi-directional reflectances of marine liquid water clouds, as measured by the Multiangle Imaging SpectroRadiometer (MISR), are compared with planeparallel radiative transfer model calculations. We define an angular consistency test that requires measured and modeled radiances to agree within ±5% for all chosen view angles for the observations to be classified as planeparallel. When all nine MISR angles are used at the full 275 m resolution, 1 in 6 pixels (17%) pass the test. There is a slight dependence on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 22 publications
0
41
0
Order By: Relevance
“…Similarly, Barker and Li (1997) reported significant deviations from 1-D radiative transfer due to horizontal photon transport if the horizontal dimensions of a considered atmospheric column are decreased. Horvath and Davies (2004) provided further evidence for the relevance of 3-D radiative effects through the observed anisotropy in the reflected solar radiation, which increasingly deviates from 1-D radiative transfer if the spatial resolution of the satellite is increased. Zinner and Mayer (2006) reported that at 1 km scale, the errors associated with horizontal photon transfer and the plane-parallel approximation cancel at least to some degree for stratiform boundary layer clouds.…”
Section: Spatial Representativeness Of a Point Measurementmentioning
confidence: 83%
“…Similarly, Barker and Li (1997) reported significant deviations from 1-D radiative transfer due to horizontal photon transport if the horizontal dimensions of a considered atmospheric column are decreased. Horvath and Davies (2004) provided further evidence for the relevance of 3-D radiative effects through the observed anisotropy in the reflected solar radiation, which increasingly deviates from 1-D radiative transfer if the spatial resolution of the satellite is increased. Zinner and Mayer (2006) reported that at 1 km scale, the errors associated with horizontal photon transfer and the plane-parallel approximation cancel at least to some degree for stratiform boundary layer clouds.…”
Section: Spatial Representativeness Of a Point Measurementmentioning
confidence: 83%
“…These other potential error sources are numerous and include r e biases due to sub-pixel heterogeneity (Zhang and Plantnick, 2011;Zhang et al, 2012Zhang et al, , 2016; 3D radiative effects (Marshak et al, 2006); assumptions regarding the degree of cloud adiabaticity (f ad in Eqn. 10; Janssen et al, 2011;Merk et al, 2016); the choice of k value (assumed constant; Brenguier et al, 2011;Merk et al, 2016); the assumption of a vertically uniform N d ; the assumed droplet size distribution shape and width (Zhang, 2013); viewing geometry effects (Várnai and Davies, 1999;Horváth, 2004;Varnai and Marshak, 2007;Kato and Marshak, 2009;Liang et al, 2009;Di Girolamo et al, 2010;Maddux et al, 2010;Liang and Girolamo, 2013;Grosvenor and Wood, 2014;Liang et al, 2015;Bennartz and Rausch, 2017); upper level cloud and aerosol 10 layers (Haywood et al, 2004;Bennartz and Harshvardhan, 2007;Davis et al, 2009;Meyer et al, 2013;Adebiyi et al, 2015;Sourdeval et al, 2013Sourdeval et al, , 2016, etc. These errors have the potential to bias N d in a way that opposes the positive bias expected from the vertical penetration effect such that the overall biases may cancel out.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the LUT is calculated for a plane-parallel cloud field using a 1-D radiative transfer model that does not consider the influence of the 3-D structure of clouds. However, Horváth (2004) found that no more than 17 % of the pixels containing marine liquid water clouds are plane-parallel objects, suggesting that the retrieval error arising from the solar-viewing geometry cannot be neglected (Zinner et al, 2010;Wolters et al, 2010;VantHull et al, 2007;Di Girolamo et al, 2010). The effects of cloud horizontal homogeneity also make the retrieval more complex.…”
Section: Introductionmentioning
confidence: 99%